Interpretação: objetivo e método da ciência de B. F. Skinner - Malavazzi, Dante Marino (2018)
A literature review showed divergences regarding the goals and methods of B. F. Skinner’s science. In particular, interpretation was sometimes framed as a goal, and other times referred to as a method. In any case, it is an activity to which Skinner devotes much of his work, although less explored by behavior analysts. Considering the relevance of the theme and the gaps in the field, this research had the general purpose of presenting Skinner’s vision of interpretation, both as goal and method. At the same time, it had as specific purposes (a) to define interpretation, according to Skinner; (b) to point out when and how the author defends its accomplishment; (c) to relate interpretation with other goals and methods proposed by Skinner; (d) to indicate the contributions and limits of interpretation, according to the author. In this regard, I examined 50 texts of Skinner related to the subject, published between 1931 and 1990. First, I read the selected texts, in chronological order and in full, highlighting the excerpts related to the research problem. Then, I reread only the excerpts and made a file for each text, in which I synthesized Skinner's position on the research problem. Lastly, I read the files in chronological order and grouped the data by decades, assigning a subtitle to each period. As much as for goal as it is for method, I argue that interpretation offers theoretical, methodological and technological contributions to Skinner’s science, although it presents limits as an inferential and speculative nature, as well as the plausible and sometimes temporary format. In my view, it is a goal equivalent to the others and a method comparable to the experimental analysis